Effect of Secondary Infections and Risk Factors on the Outcome of Covid-19 Patients in the Intensive Care Unit - Salma, Aisyah Dhiya; -, Arifin; Saptawati, Leli (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: Coronavirus Disease 2019 (Covid-19) is an infection caused by a virus with a high virulence level, which has progressively become a pandemic. Several studies have shown that risk factors and comorbidities associated with the disease can lead to severe and critical pneumonia requiring ICU treatment. This indicates that a proper understanding is needed in selecting the right therapy and determining patient prognosis. Therefore, this study aims to analyze the risk factors affecting the outcome of Covid-19 patients in the ICU of Regional General Hospital Dr. Moewardi Surakarta.Methods: This was a retrospective cross-sectional study with a total sampling technique. The risk factors analyzed included old age, hypertension, cardiovascular disease, diabetes mellitus, Invasive Mechanical Ventilators (IMV) use, and secondary infections. Data collection was carried out by reading medical records, as well as blood and/or sputum culture results of Covid-19 patients at the study location from March-October 2020. The data obtained were then analyzed using the chi-square statistical analysis and logistic regression (α = 0.05) with SPSS software version 21.Results: Based on the chi-square test, ventilator type (p<0.001), and secondary infection (p=0.004) were statistically associated with the outcome of Covid-19 patients. Meanwhile, age (p=0.739), hypertension (p=0.202), cardiovascular disease (p=0.073), and diabetes mellitus (p=0.124) had no statistical relationship. The logistic regression test results showed that IMV was a risk factor for Covid-19 death and secondary infection was associated with mortality.Conclusion: The ventilator type and secondary infection had a significant relationship with the outcome of Covid-19 patients. Furthermore, IMV use was a risk factor for mortality among infected people.